Association of biological aging acceleration transitions and burdens with incident cardiovascular disease: longitudinal insights from a national cohort study - Xin Zhang; Yu Yan; Yuxin Liu; Zixin Wang; Yuchen Jiang; Shuo Zhang; Tongda Xu; Ke Wang; Chu Zheng; Ping Zeng (BMC Medicine)
Abstract Background Previous studies have examined the association between biological aging acceleration (BioAgeAccel) and cardiovascular disease (CVD). However, the effects of BioAgeAccel transitions and burdens on CVD risk remained unclear, and little was known about the association of BioAgeAccel with age at CVD onset. Methods We included 316,417 participants from the UK Biobank in the baseline analyses and reserved 7249 in the visit-to-visit analyses. BioAgeAccel was defined as the residual derived from a linear regression of biological age against chronological age, with higher values indicating accelerated aging. We defined BioAgeAccel transitions based on aging status at baseline and the first follow-up, and created three indicators to reflect BioAgeAccel burdens. Cox models were used to evaluate the associations of baseline BioAgeAccel, BioAgeAccel transitions, and BioAgeAccel burdens with incident CVD risk. Linear models were employed to investigate their impacts on age at CVD onset. Results Compared to individuals maintaining stable non-accelerated aging patterns, those transitioning to accelerated aging status showed a 29.8% (4.2–61.8%) increased CVD risk, while participants with sustained accelerated aging demonstrated a more pronounced 65.5% (35.9–101.5%) risk elevation. Reversal from accelerated to non-accelerated aging status was associated with a significant 25.6% (3.9–42.3%) risk reduction compared to persistent accelerated aging. Higher BioAgeAccel burdens were related to enhanced incidence and advanced onset of CVD, all of which were greater than the effect of baseline BioAgeAccel, with cumulative BioAgeAccel showing the greatest influence on CVD risk (HR = 1.26 [1.07–1.47]) and the most pronounced contribution to earlier onset of CVD (0.989 [0.558–1.420] years). BioAgeAccel burdens were associated with a higher CVD risk compared to FRS or SCORE2 burdens and could enhance the predictive capacity of the two risk scores. Drug treatments did not substantially impact these results. We further discovered socioeconomic status likely antagonized the associations of BioAgeAccel burdens with CVD. Conclusions This study revealed BioAgeAccel progression was associated with a higher incident CVD risk, while its reversal was linked to a lower risk. BioAgeAccel burdens were associated with increased risk and earlier onset of CVD, exceeding the effects of baseline BioAgeAccel and some well-known risk scores, and cumulative BioAgeAccel exhibited the strongest impact among them.